Civil-military relations in Southeast Asia - Croissant, Aurel (Cambridge University Press, 2018)
Civil-Military Relations in Southeast Asia reviews the historical origins, contemporary patterns, and emerging changes in civil-military relations in Southeast Asia from colonial times until today. It analyzes what types of military organizations emerged in the late colonial period and the impact of colonial legacies and the Japanese occupation in World War II on the formation of national armies and their role in processes of achieving independence. It analyzes the long term trajectories and recent changes of professional, revolutionary, praetorian and neo-patrimonial civil-military relations in the region. Finally, it analyzes military roles in state- and nation-building; political domination; revolutions and regime transitions; and military entrepreneurship
Title from publisher's bibliographic system (viewed on 24 Sep 2018)
Gesehen am 09.03.2021
Keywords: Geschichte; Militärpolitik; Staat; Militär; Südostasien